2018
DOI: 10.1007/s00330-018-5538-4
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular global myocardial strain assessment comparing the reproducibility of four commercially available CMR-feature tracking algorithms

Abstract: • Different software packages are currently available for myocardial strain assessment using routinely acquired cine CMR images. • Global myocardial strain values are not interchangeable between vendors for global longitudinal and global radial strain. • Inter- and intra-observer reproducibility for global strain assessment is excellent. However, some vendors encounter problems to reproducibly measure global radial strain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 26 publications
7
58
0
Order By: Relevance
“…In comparison, reproducibility of segment was superior to TomTec and even comparable to tagging. These results are in line with a previous report by Barreiro-Perez et al [12], who investigated inter-vendor agreement of optical flow-based strain-assessment software and found a clear outperformance of segment in comparison to the other software vendors.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In comparison, reproducibility of segment was superior to TomTec and even comparable to tagging. These results are in line with a previous report by Barreiro-Perez et al [12], who investigated inter-vendor agreement of optical flow-based strain-assessment software and found a clear outperformance of segment in comparison to the other software vendors.…”
Section: Discussionsupporting
confidence: 93%
“…Optical flow-based strain assessment is increasingly being employed to assess myocardial strain in both scientific and clinical settings as part of a comprehensive CMR [6,11], data regarding direct comparisons of the different strain computation algorithms is sparse, especially for regional data [12]. Furthermore, this is the first direct comparison of different optical flowstrain analysis algorithms including an additional comparison with tagging, the reference standard for strain assessment [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the healthy subjects GRS values were slightly higher, and GCS and GLS slightly lower, compared to a meta-analysis of CMR FT derived strain values in normal subjects [23]. Although a high degree of interobserver reproducibility in the CMR assessment of strain has been previously demonstrated [24], recognized variations in strain on images obtained at different field strengths and significant variability across postprocessing software vendors [25] may account for these differences.…”
Section: Discussionmentioning
confidence: 77%
“…Longitudinal strain was not calculated since not all patients had all the necessary acquisitions for its estimation, namely long-axis, 2-, 3-, and 4-chamber cine sequences. Radial strain was not included in the study because it has shown subpar reproducibility in previous analyses (31). Conversely, circumferential strain only requires short-axis cine sequences which were available in all patients and has shown satisfactory reproducibility in previous studies.…”
Section: Discussionmentioning
confidence: 99%